Biocrude production through hydro‐liquefaction of wood biomass in supercritical ethanol using iron silica and iron beta zeolite catalysts. Issue 11 (6th September 2019) - Jogi, Ramakrishna; Mäki‐Arvela, Päivi; Virtanen, Pasi; Kumar, Narendra; Hemming, Jarl; Smeds, Annika; Lestander, Torbjörn A; Mikkola, Jyri‐Pekka
Abstract: Background: In the production of biofuels from lignocellulosic material, biocrude plays a key role. The present work deals with the biocrude production through hydrothermal liquefaction (HTL) of birch wood in supercritical ethanol over 5 wt% Fe‐H‐Beta‐150 (SiO2 to Al2 O3 ratio of 150) or 5 wt% Fe‐SiO2 catalyst. Results: The liquid and solid products were characterized with various analytical techniques such as gas chromatography mass spectrometry (GC–MS), gas chromatography with a flame ionization detector (GC‐FID), size exclusion chromatography (SEC), inductively‐coupled plasma mass spectrometry (ICP‐MS), powder X‐ray diffraction (p‐XRD), scanning electron microscopy (SEM), and solid‐state carbon‐13 magic angle spinning nuclear magnetic resonance ( 13 C‐MAS‐NMR), respectively. The results revealed that 5 wt% Fe‐H‐Beta‐150, a strongly Brønsted acidic catalyst, enhanced the biocrude formation when compared with a non‐acidic 5 wt% Fe‐SiO2 catalyst. Hemicellulose and lignin degradation occurred resulting in formation of mainly sugars, acids‐esters and phenolic compounds in the liquid phase. The gaseous atmosphere of hydrogen also enhanced the degradation of biomass. The biocrude yield from birch was 25 wt% over 5 wt% Fe‐H‐Beta‐150. The Brønsted acidic catalyst gave higher dissolution efficiency and its clear catalytic effect was observed in comparison to non‐acidic 5 wt% Fe‐SiO2 . The degradation level of lignin in the presence of 5 wt% Fe‐H‐Beta‐150 was high 68 wt% aromatic products were formed, while only 38 wt% was obtained with 5 wt% Fe‐SiO2 . Conclusions: Hydrogen atmosphere enhances the fractionation of birch wood when compared to argon atmosphere. The 5 wt% Fe‐H‐Beta‐150 catalyst enhanced very strongly the degradation of hemicellulose and lignin in biomass to sugars and acid‐esters as well as phenolic compounds, respectively, compared to the non‐acidic 5 wt% Fe‐SiO2 catalyst. © 2019 Society of Chemical Industry